Fast food consumption and obesity: Relationship among elementary school students in Yogyakarta - Djauhar Ismail; E. S. Herini; Pudjo Hagung; Tonny Sadjimin (Indonesian Pediatric Society, 1999)
Excessive consumption of calories particularly those of fast foods incompanson to energy expenditure is considered to be an important cause of obesity in children both in developed and developing countries. The objective of this study was to measure the association between the pattern of consuming fast food and the incidence of obesity in elementary school students in an urban developing counUy setting. Across sectional study was conducted to students from 30 elementruy schools in Yogyakarta, lndonesra, who were selected by a population proportional multistage cluster random sampling. From the sample of 3575 parents, 3258 returned self fulfilled questionnaires, a response rate of 91.1%. There was a statistically significant assoctaion between obesity and the experience of consuming fast food (odds ratio 2.82; 95%CI 2.08;3.82), the attitude towards fast food (odds ratio 1.88; 95%CI 1.31; 2.69) and the frequency of consumption of fast food (p < 0.001).